2021
DOI: 10.1136/bmjdrc-2020-002097
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of a self-management and comprehensive training intervention in patients with type 2 diabetes up to 5 years of diagnosis in a specialized hospital in Mexico City

Abstract: IntroductionTo assess the cost-effectiveness of a multidisciplinary and comprehensive innovative diabetes care program (CAIPaDi) versus usual treatment in public health institutions.Research design and methodsUsing a cost-effectiveness analysis, we compared the CAIPaDi program versus usual treatment given in Mexican public health institutions. The analysis was based on the IQVIA Core Diabetes Model, a validated simulation model used to estimate long-term clinical outcomes. Data were prospectively obtained from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“… 28 Concurrently, novel interventions have been introduced and evaluated in Mexico to attain metabolic objectives, resulting in preservation of treatment goals. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“… 28 Concurrently, novel interventions have been introduced and evaluated in Mexico to attain metabolic objectives, resulting in preservation of treatment goals. 29 , 30 …”
Section: Discussionmentioning
confidence: 99%
“…The progression of relevant physiological parameters (eg, HbA 1c , systolic blood pressure, lipids, and BMI) is simulated based on long-term epidemiological data, and event risk is constantly updated on the basis of these risk factors. The model facilitates interconnectivity and interaction between the modeled complications, representing the complex and varied sequelae of diabetes [19].…”
Section: Discussionmentioning
confidence: 99%
“…A minimum approach is applied to the estimation of utilities-in the case of multiple events, the lower utility is applied for that period. This is a simple and well-established approach to the application of utilities in the case of multiple interdependent health states [17,19].…”
Section: Discussionmentioning
confidence: 99%
“…This study provides supporting evidence that an integrated diabetes care model is beneficial for increasing the skills and confidence of GPs in delivering best practice and evidence-based care for diabetes management. Evidence from studies conducted in Australia [30,31] and internationally [32,33] have shown that integrated healthcare delivery in primary care is cost-effective compared to usual models of care. Some GPs reported that the additional time taken for the preparation of case-conferences can be burdensome; however, it seemed that much of that time was needed for updating pathology, eye, and podiatry reviews which is a routine part of diabetes care.…”
Section: Discussionmentioning
confidence: 99%